Effect of high‐fructose corn syrup on the acidogenicity, adherence and biofilm formation of Streptococcus mutans. (28th May 2013) - Ma, R; Sun, M; Wang, S; Kang, Q; Huang, L; Li, T; Xia, W‐W
Abstract Background Although high‐fructose corn syrup (HFCS) as a kind of sugar has been widely used in manufactured foods recently, there is little information available regarding its cariogenicity. The aim of this study was to evaluate the cariogenic potential of HFCS. Methods Streptococcus mutans UA159 was inoculated into HFCS media and cultivated. The pH of each culture was measured to assess acidogenicity. Spectrophotometric turbidity was measured to determine the percentage of adherence. Confocal laser scanning microscopy and SYTO‐9 staining were employed to observe biofilm formation. Sucrose media was used as a positive control. Results The ΔpH in HFCS media was significantly larger than that in sucrose media and the pH in HFCS media decreased faster (p < 0.05). The percentage of adherence of S. mutans in HFCS media was significantly lower than that in sucrose media (p < 0.05). The biofilm formed in sucrose media was significantly thicker than that in HFCS media (p < 0.05). Conclusions The results of this study suggest that the cariogenicity of S. mutans in the presence of HFCS may differ compared to its cariogenicity in the presence of sucrose. Further in vivo studies need to be undertaken to resolve this uncertainty.